Предмет: Алгебра,
автор: Аноним
помогите пж!!!!!!!!!!!!!!!!!!
Приложения:
Ответы
Автор ответа:
1
Ответ:
В решении.
Объяснение:
1) Преобразовать выражение для упрощения:
а) 7х⁻² = 7/х²;
6 - х⁻² = 6 - 1/х² = (6х² - 1)/х²;
7/х² : (6х² - 1)/х² = 7/ (6х² - 1) - первая дробь;
б) 7х⁻² = 7/х²;
6 + х⁻² = 6 + 1/х² = (6х² + 1)/х²;
7/х² : (6х² + 1)/х² = 7/ (6х² + 1) - вторая дробь;
в) х = 0,1⁻¹ = 1/0,1;
г) 7/ (6х² - 1) - 7/ (6х² + 1) =
общий знаменатель (6х² - 1)(6х² + 1);
= (7 * (6х² + 1) - 7 * (6х² - 1))/((6х² - 1)(6х² + 1)) =
= (42х² + 7 - 42х² + 7)/(36х⁴ - 1) =
= 14/(36х⁴ - 1) =
= 14/(36 * (1/0,1)⁴ - 1) =
= 14/(36 * 1/0,0001 - 1) =
= 14/(360000 - 1) =
= 14/359999.
Похожие вопросы
Предмет: Русский язык,
автор: Мирочка11
Предмет: Окружающий мир,
автор: Elenka006
Предмет: Русский язык,
автор: Rio1111777888
Предмет: Литература,
автор: Probl
Предмет: Русский язык,
автор: reks6